(untitled) (Baghdad Science Journal, 2023)
Microorganisms establish both structural and functional construction in the marine environment, despite scientific advances, the identification of marine bacterial species is still considered as a common challenge in microbiology. Nevertheless, the present study aims to make an effort, although it seems modest, but it could establish a basis for studying the bacterial diversity in the Iraqi marine area, because of what this aspect entails of the poverty of studies related to this aspect in the studied area. The current results show the marine studied area are classified within worming area, where the average temperature ranged from 23.17 to 26.17 ºC. The recorded number of bacteria was increased with temperature increasing (0.210, 0.250, 0.305, 0.517, 0.553 and 0.625) through the studied period (January, February, March, April, May and June) respectively. The results showed that the identified bacteria were related to three bacterial phyla(Firmicutes, Proteobacteria, and Actinobacteria),with the clear superiority to the phyla (Firmicutes).The most occurrence bacterial genera were( Staphylococcus lentus, Vibrio parahaemolyticus, Vibrio alginolyticus, Sphingomonus paucimobilis and Aeromonas hydrophila/caviae), which have different percentage of frequency ,(50,40,60,30 and 20%) respectively. The present discoveries provide initial evidence on the bacterial diversity in the Iraqi marine waters. Further studies are necessary to make a more comprehensive image of bacterial diversity within these marine regions. Running Tittle: Marine Bacterial Diversity